Super capacitor electrode material and preparation method thereof

By growing a composite electrode material of nickel cobalt sulfur oxygen complex Co2NiO4//CoNi2S4@CNT and carbon nanotubes on a conductive substrate, the problems of low specific capacity and unstable capacitance performance of existing supercapacitor electrode materials are solved, and high specific capacity is achieved. capacity and good cycling stability.

CN119361332AActive Publication Date: 2025-01-24SHANGHAI UNIVERSITY OF ELECTRIC POWER
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411487913.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The specific capacity of the existing supercapacitor electrode materials is relatively low, and the capacitance performance is unstable under high current density, which requires improvement of specific capacity and cycling stability.

Method used

CO2NIO4 // CONI2S4@CNT is used as electrode materials. The electrical active nano structure is directly growing on the conductive base through one -step AC electrococcion deposition method, combined with the support of carbon nanotubes to form a three -dimensional nano -like loose porous structure.

Benefits of technology

The specific capacity and cycle stability of the supercapacitor are significantly improved, the supercapacitor can maintain excellent electrochemical performance under high scan speed and high current density, and the preparation process is simple and time-consuming.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361332A_ABST
    Figure CN119361332A_ABST
Patent Text Reader

Abstract

The invention relates to a supercapacitor electrode material and a preparation method thereof. The supercapacitor electrode material is a nickel-cobalt-sulfur-oxygen composite metal compound loaded on a conductive substrate, the specific capacity of the supercapacitor electrode material reaches 7247.9 F / g under the current density of 1A / g, and the supercapacitor electrode material has ultrahigh specific capacity which is far higher than the capacitance of similar metal sulfur oxide materials and has good cycle stability (the capacitance retention rate is 79% after 5000 cycles under the current density of 5A / g). The obtained large-capacitance electrode material can be obtained in a short time (about one hour) through a one-step alternating current electrodeposition method, and compared with an existing hydrothermal growth method, chemical precipitation, electrodeposition and other multi-step synthesis methods, the method is easy to operate, short in consumed time, simple and feasible in preparation process and suitable for industrial production. And great possibility is provided for applying the electrode material to an energy storage device and further putting the electrode material into use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitor electrode material preparation, and in particular to a supercapacitor electrode material and a preparation method thereof. Background Art

[0002] With the reduction of fossil fuel reserves, the deterioration of human living environment and the development and utilization of non-renewable energy, efficient energy storage devices are urgently needed. Among various electrochemical energy conversion and storage technologies, supercapacitors (SCs) are widely used in electrical energy storage due to their advantages such as fast charge and discharge rate, good cycle stability and ultra-high power density. Supercapacitors are a new type of energy storage device that can be used in energy storage devices, power supply systems and many electronic devices. The application areas of supercapacitors include new energy vehicles, smart wearable devices, power system energy storage, etc. Generally, supercapacitors (SCs) can be divided into electric double layer capacitors (EDLCs) and pseudocapacitors according to different energy storage mechanisms. Among different types of supercapacitors, hybrid supercapacitors (SCs) composed of a battery-like positive electrode and an activated carbon negative electrode have attracted great attention. They can store energy through fast redox reactions. The capacitance and energy density of hybrid supercapacitors are at least one order of magnitude higher than those of electric double layer capacitors. These advantages provide a promising strategy to improve the high energy and power density of super hybrid capacitors. The performance of hybrid supercapacitors is closely related to the performance of their battery-type cathode materials. Therefore, finding and designing suitable cathode materials is the key to achieving excellent performance of hybrid supercapacitors.

[0003] Transition metal sulfides are widely used as electrode materials in energy storage materials due to their excellent electrochemical properties, high conductivity, unique nanostructure and good physical and electrochemical properties. Their high capacitance comes from a variety of sulfidation states that can consume or generate more electrons in redox reactions, and studies have found that the combination of two or more metal compounds can produce significant synergistic effects, usually showing better electrochemical properties than the corresponding single metal sulfides. In the nickel-cobalt-based material system, nickel ions can promote the electrochemical activity of the material, while cobalt ions can reduce the charge transfer resistance and enhance the stability of the material, resulting in excellent specific capacitance and rate performance. Due to the interaction between nickel ions and cobalt ions, bimetallic nickel-cobalt sulfides show better rate performance than single metal cobalt sulfide and nickel sulfide. So they are very popular battery-type electrode materials for hybrid supercapacitors.

[0004] As a representative ternary transition sulfide, NiCo2S4 has been widely studied as an electrode material for supercapacitors or lithium-ion batteries. For example, Jing et al. prepared CoNi2S4 nanosheets by hydrothermal and sulfonation methods and showed good performance at a current density of 1 A g -1The capacitance is 1136.5F g -1 Wang et al. integrated Co3S4 and NiS through a hydrothermal reaction and achieved a significant synergistic reaction. Therefore, the Co3S4@NiS nanoplate electrode as a capacitor positive electrode material exhibited high energy density and a wide voltage window. Chen et al. prepared a special NiCo2S4 structure with a sea urchin-like morphology through a precursor conversion method. At a current density of 1A g -1 1149F g was obtained -1 The specific capacitance at 20A g -1 After 5000 cycles under low temperature, the capacitance retention rate reached 91.4%. Wang et al. reported hierarchical NiCo2S4 nanostructures with controllable mass loading, demonstrating that the nanostructured NiCo2S4 with low mass loading (0.53 mg cm -2 The specific capacitance of the electrode reaches 2732 F g -1 Zhang et al. successfully synthesized urchin-shaped, flower-shaped, tubular, and cubic NiCo2S4 structures using different solvents through a simple shape-controlled hydrothermal route. The specific capacitance is 3A g -1 The current density can reach 1048F g -1 At 10A g -1 After 5000 charge-discharge cycles at a current density of 1.50, it maintained 75.9% of its initial capacitance. Shen et al. successfully composited CoO-NiO-PPY electrode materials on carbon cloth by AC electrodeposition. -1 The capacitance can reach 1123F g at a current density of -1 , and the capacitance retention rate after 5000 cycles is 90.1%. However, the specific capacity of supercapacitors prepared from these electrode materials is still low, and after comparing the charge and discharge capacitance under different current densities, it is found that the capacitance attenuation of existing supercapacitor materials under large currents is relatively serious, that is, the capacitance performance under high current density is not very stable and needs to be improved. Summary of the invention

[0005] The purpose of the present invention is to provide a supercapacitor electrode material and a preparation method thereof to improve specific capacity and cycle stability.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] On the one hand, the present invention provides a supercapacitor electrode material, comprising: a conductive substrate and a metal composite loaded on the conductive substrate; the metal composite is a nickel-cobalt-sulfur-oxygen composite, and the supercapacitor electrode material is a loose porous structure composed of three-dimensional nanosheets.

[0008] Preferably, the nickel-cobalt-sulfur-oxygen composite is Co2NiO4 / / CoNi2S4@CNT, and the conductive substrate comprises nickel foam.

[0009] Further preferably, the structure of the Co2NiO4 / / CoNi2S4@CNT is a composite of nickel cobalt oxide and sulfide coated with carbon nanotubes.

[0010] Preferably, the CNT in the Co2NiO4 / / CoNi2S4@CNT refers to a single-walled carbon nanotube.

[0011] In the present invention, the electrode material prepared by using Co2NiO4 / / CoNi2S4@CNT to load on a conductive substrate has a three-dimensional structure in the form of nanosheets, which can effectively increase the specific surface area, increase the active sites of the redox reaction, and is more conducive to the transmission of ions and electrons. At the same time, the electrode material of the present invention has a large voltage window (up to 0.6V) and specific capacity. Applying it to supercapacitor electrodes can improve energy density and solve the technical problem of low energy density of existing supercapacitors. The asymmetric supercapacitor using Co2NiO4 / / CoNi2S4Ni-Co-S@CNT composite metal sulfur oxide electrode and activated carbon as the counter electrode shows a high energy density of 178.8Wh / kg at a power density of 1516.5W / kg. In addition, the structure in which the metal composite is directly loaded on the conductive substrate does not require a binder and a conductive agent, thereby improving the electrochemical stability and rate performance of the supercapacitor.

[0012] In a second aspect, the present invention also provides a method for preparing the above-mentioned supercapacitor electrode material, comprising the following steps: subjecting a metal precursor to an electrodeposition reaction on a conductive substrate, washing and drying, and then coating the surface of the conductive substrate after the electrodeposition reaction with a single-walled carbon nanotube slurry to obtain the supercapacitor electrode material.

[0013] The present invention deposits a composite material of composite Ni-Co sulfide by a one-step alternating current electrodeposition method. In this process, nickel foam is used as a substrate (collector) and a nickel source, and based on the in-situ redox reaction of nickel and sulfur during the electrodeposition process, direct growth of a nickel-cobalt-sulfur-oxygen composite electrode can be achieved without adding additional salt as a nickel source and without a binder. This indicates that the electrode preparation process, including the careful grinding and coating procedures required for powdered active materials, becomes unnecessary. In contrast, the preparation method of the present invention has simple steps, and the capacitive performance of the electrode material prepared by the present invention has a greater advantage.

[0014] Preferably, the metal precursor is prepared by mixing cobalt nitrate and thiourea in a solvent, and the molar ratio of the cobalt nitrate to thiourea is in the range of (1-5):(5-10).

[0015] More preferably, the molar ratio of the cobalt nitrate to thiourea is (1-3):(5-8).

[0016] Further preferably, the cobalt nitrate and thiourea are mixed in a solvent by magnetic stirring for 20 to 45 minutes.

[0017] Further preferably, the cobalt nitrate is used as the cobalt source, and the thiourea is used as the sulfur source.

[0018] More preferably, the solvent is deionized water.

[0019] Preferably, the nickel foam substrate is used as a nickel source, and the size of the nickel foam is 1×2 cm.

[0020] Preferably, the electrodeposition reaction uses the metal precursor as an electrolyte, and is deposited for 30 min to 90 min at a potential range of 6-20 V, an AC frequency of 40 Hz to 100 Hz, and a temperature of 25° C. to 50° C.

[0021] Further preferably, the electrodeposition refers to a one-step AC electrodeposition method, which is an electrochemical deposition technology that uses an AC electric field to cause metal ions in a solution to deposit on the electrode surface to form a thin film or coating, completing the deposition process in one step.

[0022] More preferably, the electrodeposition reaction is carried out in a two-electrode system. In the present invention, the two-electrode system refers to using clean nickel foam (NF) as a working electrode and a graphite electrode as a counter electrode.

[0023] Preferably, the coating of the single-walled carbon nanotube slurry comprises absorbing the single-walled carbon nanotube slurry to penetrate the surface of the conductive substrate after the electrodeposition reaction, and then vacuum drying to obtain the supercapacitor electrode material.

[0024] Preferably, the single-walled carbon nanotube slurry is prepared by a CVD method, and the volume of the single-walled carbon nanotube slurry coating is 0.15-0.25 mL.

[0025] Further preferably, the CVD method (Chemical Vapor Deposition) is a material synthesis technology that heats a substrate in a gas environment containing a catalyst or other reaction accelerators so that the chemical substances in the gas react and deposit a solid film or material on the substrate.

[0026] Preferably, the conductive substrate is subjected to the following pretreatment steps to remove the oxide layer and other impurities on the surface: the conductive substrate is subjected to ultrasonic reaction in an acid solution, acetone, deionized water and anhydrous ethanol in sequence.

[0027] Further preferably, the acidic solution comprises 1-3 mol / L dilute hydrochloric acid.

[0028] Further preferably, the conductive substrate is ultrasonically reacted in an acidic solution, acetone, deionized water and anhydrous ethanol for 15 to 20 minutes respectively.

[0029] In a third aspect, the present invention further provides a supercapacitor electrode, comprising the above-mentioned electrode material.

[0030] Compared with conventional electrodes, the supercapacitor electrode of the present invention has good mechanical adhesion, fast electron transport and more efficient ion diffusion, and does not require adhesives or conductive additives. It provides ideal conditions for full contact with the electrolyte, preventing the entire electroactive material from significant collapse and disintegration during the redox reaction process with drastic and frequent phase changes. In addition, carbon nanotubes are added to support the pores, thereby bringing higher efficiency to electrochemical energy storage.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The present invention provides an electrode material, comprising a nickel foam conductive substrate and a Co2NiO4 / / CoNi2S4@CNT metal composite loaded on the conductive substrate, and having a stable three-dimensional structure with a nanosheet morphology, which can effectively increase the specific surface area, increase the active sites of the redox reaction, and be more conducive to the transmission of ions and electrons, thereby improving the specific capacity of the supercapacitor.

[0033] (2) The present invention uses a one-step AC electrodeposition method to directly grow the electroactive nanostructure as a non-binding electrode material on a conductive substrate without the need for a binder or a conductive agent, which can effectively reduce the equivalent series resistance and improve the electrochemical stability and rate performance of the supercapacitor.

[0034] (3) The carbon nanotubes added in the present invention support the pore structure of the sulfide, thereby enabling the supercapacitor to have a higher specific capacity and good cycle performance.

[0035] (4) Under high scan rate, the supercapacitor electrode prepared by the present invention can still maintain the redox peak. At a current density of 1 A / g, its specific capacity reaches 7247.9 F / g, with ultra-high specific capacity and stable cycle performance. At a current density of 5 A / g, the capacitance retention rate is 79% after 5000 cycles.

[0036] (5) The high-capacitance electrode material obtained by the present invention can be obtained in a short time (about one hour) by a one-step alternating current electrodeposition method. Compared with the existing preparation process, the present invention is simple to operate and takes less time, which provides great possibilities for the application of electrode materials in energy storage devices and further put into practical use. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the XRD diagram of the Co2NiO4 / / CoNi2S4@CNT electrode material in Example 1 of the present invention;

[0038] Figure 2 This is the SEM image of the Co2NiO4 / / CoNi2S4@CNT electrode material in Example 1 of the present invention (scale is 500nm);

[0039] Figure 3 This is the SEM image of the Co2NiO4 / / CoNi2S4@CNT electrode material in Example 1 of the present invention (scale is 2 μm);

[0040] Figure 4 HRTEM image of Co2NiO4 / / CoNi2S4@CNT electrode material in Example 1 of the present invention;

[0041] Figure 5 This is the SAED pattern of the Co2NiO4 / / CoNi2S4@CNT electrode material in Example 1 of the present invention;

[0042] Figure 6 The cyclic voltammograms of the supercapacitor electrode at different scan rates in Example 1 of the present invention;

[0043] Figure 7 This is a constant current charge and discharge diagram of the supercapacitor electrode at different current densities in Example 1 of the present invention;

[0044] Figure 8 This is the SEM image of the Co2NiO4 / / CoNi2S4@CNT electrode material in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0046] The present invention provides a supercapacitor electrode material, comprising: a foamed nickel conductive substrate and a Co2NiO4 / / CoNi2S4@CNT nickel-cobalt-sulfur-oxygen composite loaded on the conductive substrate. The supercapacitor electrode material is a loose porous structure composed of three-dimensional nanosheets.

[0047] The above-mentioned supercapacitor electrode material is obtained by the following steps:

[0048] S1, dissolving cobalt nitrate and thiourea in a molar ratio of (1-5):(5-10) in deionized water, and mixing with magnetic stirring for 20-45 minutes to prepare a metal precursor solution;

[0049] S2, ultrasonically treating the nickel foam conductive substrate in an acid solution, acetone, deionized water and anhydrous ethanol for 15 to 20 minutes respectively.

[0050] S3, using the metal precursor solution obtained in step S1 as an electrolyte, an electrodeposition reaction is carried out on a conductive substrate: at a potential range of 6-20V, an AC frequency of 40Hz to 100Hz and a temperature of 25°C to 50°C, the deposition time is 30min to 90min. After the reaction is completed, the electrode is washed and dried.

[0051] S4, coating the surface of the electro-deposited nickel foam conductive substrate obtained in S3 with 0.15-0.25 mL of single-walled carbon nanotube slurry, so that the surface of the nickel foam conductive substrate is impregnated with the single-walled carbon nanotube slurry, and vacuum drying to obtain the Co2NiO4 / / CoNi2S4@CNT supercapacitor electrode material.

[0052] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0053] In the following examples, the single-walled carbon nanotubes used were purchased from Guosen Linghang New Materials, model GS168-S04C, with a tube diameter of 1-2 nm, a length of 5-20 μm, and a specific surface area of ​​700-1000 m 2 / g.

[0054] Example 1

[0055] (1) The following solutes were weighed using a precision balance: 0.58206 g Co(NO3)2·6H2O and 0.5 g CH4N2S, with a molar ratio of about 2:7. 40 ml of deionized water was taken as the solvent, and the solvent and solute were magnetically stirred for 30 min and then ultrasonically mixed for 30 min.

[0056] (2) The nickel foam was placed in 3 mol / L dilute hydrochloric acid, acetone, deionized water, and anhydrous ethanol, and ultrasonicated for 20 min respectively to remove the surface oxide layer and impurities, thereby obtaining a pretreated nickel foam.

[0057] (3) Pour the solution prepared in step (1) into the cup of the electrolytic cell, clamp the pretreated nickel foam with an electrode clamp as the working electrode, use the graphite electrode as the counter electrode, and immerse the two electrodes in the cup of the electrolytic cell; perform electrodeposition at a voltage of 10V, 50Hz and an alternating current frequency, at a temperature range of 25-40°C, and the deposition time is 1h. After the reaction is completed, take out the nickel foam electrode, clean it with deionized water and anhydrous ethanol, and vacuum dry it at 60°C for 12h. After drying, add 0.2ml of single-walled carbon nanotube slurry to the electrode, so that the electrode is impregnated with the single-walled carbon nanotube slurry, and then vacuum dry it overnight to obtain a Co2NiO4 / / CoNi2S4@CNT composite electrode material grown on nickel foam.

[0058] Performance Testing

[0059] The XRD pattern of the Co2NiO4 / / CoNi2S4@CNT composite electrode material prepared in Example 1 is as follows: Figure 1 As shown in the figure, it can be seen that the diffraction peaks of the prepared electrode material are consistent with the diffraction peaks of the standard cards Co2NiO4 and CoNi2S4, indicating the successful preparation of the Co2NiO4 / / CoNi2S4@CNT composite electrode material.

[0060] The SEM (scanning electron microscope) image of the Co2NiO4 / / CoNi2S4@CNT composite electrode material prepared in Example 1 is as follows: Figure 2 , Figure 3 , TEM (transmission electron microscope) picture Figure 8 As shown, it means that the carbon nanotubes are successfully loaded on the Co2NiO4 / / CoNi2S4 composite material, which means that the Co2NiO4 / / CoNi2S4@CNT composite electrode material is successfully prepared in this embodiment, and the electrode material has a nano-sheet morphology.

[0061] The HRTEM (transmission electron microscopy) and SAED (selected area electron diffraction) images of the Co2NiO4 / / CoNi2S4@CNT composite electrode material prepared in Example 1 are shown in Figure 4 and Figure 5 As shown, the lattice fringe spacing is about 0.15nm and 0.26nm, corresponding to the (620) and (222) planes of NiCo2S4 (PDF00-024-0334). The lattice spacing of 0.18nm, 0.22nm and 0.24nm can be indexed to the (422), (400), (222) planes of NiCo2O4 (PDF00-020-0781). The selected area electron diffraction (SAED) pattern of Ni-Co sulfur-oxygen composite nanosheets shows a ring pattern, indicating its polycrystalline structure, and each diffraction ring can also be well pointed to the crystal plane of CoNi2S4 and NiCo2O4.

[0062] A three-electrode system was used to assemble a supercapacitor and test its electrochemical performance. The platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, the prepared Co2NiO4 / / CoNi2S4@CNT composite electrode material was used as the working electrode, and the 2M KOH solution was used as the electrolyte. The electrochemical performance of the supercapacitor electrode was tested in the Chenhua CHI660E electrochemical workstation test system, where the charge and discharge voltage range was 0 to 0.5V. The test results are shown in Figure 2. Figure 6 and Figure 7 As shown, Figure 6 The cyclic voltammograms of the supercapacitor electrode at different scan rates in Example 1 are shown in FIG. Figure 7 The constant current charge and discharge diagram of the supercapacitor electrode in Example 1 at different current densities. As can be seen from the figure, at a high scan rate, the supercapacitor electrode in Example 1 can still maintain the redox peak. According to the calculation formula of specific capacity Calculation shows that at a current density of 1 A / g, the specific capacity of the supercapacitor electrode prepared in Example 1 reaches 7247.9 F / g, which has an ultra-high specific capacity; at a current density of 5 A / g, the capacitance retention rate is 79% after 5000 cycles, which has stable cycle performance.

[0063] Comparative Example 1: Electrode material is Co2NiO4 / / CoNi2S4

[0064] This comparative example 1 is intended to investigate the effect of adding single-walled carbon nanotubes on the morphology of electrode materials. The method for preparing Co2NiO4 / / CoNi2S4 composite electrode materials and assembling supercapacitors is the same as that of comparative example 1. Compared with comparative example 1, the material after the electrodeposition reaction in step (3) is directly cleaned and dried overnight without coating with CNTs, and other conditions remain unchanged.

[0065] The Co2NiO4 / / CoNi2S4 composite electrode material obtained in this comparative example has a nanosheet morphology, the gaps between the nanosheets become smaller, and the nanosheet layers are closer together.

[0066] The electrochemical properties of the supercapacitor electrode were tested in the Chenhua CHI660E electrochemical workstation test system using the same test method as in Comparative Example 1. The specific capacity of the supercapacitor electrode in this comparative example was 4840 F / g at a current density of 1 A / g.

[0067] Comparative Example 2

[0068] This comparative example 2 is intended to investigate the effect of the amount of reaction solute on the morphology of the electrode material. The method for preparing the Co2NiO4 / / CoNi2S4 composite electrode material and assembling the supercapacitor is the same as that of comparative example 1. Compared with comparative example 1, in step (1), 0.58206 g of Co(NO3)2·6H2O and 0.7 g of CH4N2S were weighed as reaction solutes, and the molar ratio of the two was about 2:9; in step (3), the material after the electrodeposition reaction was directly cleaned and dried overnight without coating CNT, and other conditions remained unchanged.

[0069] The Co2NiO4 / / CoNi2S4 composite electrode material obtained in this comparative example 2 has a nanosheet morphology, with a larger outline, a larger nanosheet thickness, and a smaller gap.

[0070] The electrochemical properties of the supercapacitor electrode were tested in the Chenhua CHI660E electrochemical workstation test system using the same test method as in Comparative Example 1. The supercapacitor electrode in Comparative Example 2 had a specific capacity of 1896.19 F / g at a current density of 1 A / g.

[0071] Comparative Example 3

[0072] This comparative example 3 is intended to investigate the effect of the frequency of the electrodeposition reaction on the morphology of the electrode material. The method for preparing the Co2NiO4 / / CoNi2S4@CNT composite electrode material and assembling the supercapacitor is the same as that of comparative example 1. Compared with comparative example 1, in step (3), the frequency of the electrodeposition reaction is changed from 50 Hz to 60 Hz, and other conditions remain unchanged.

[0073] The Co2NiO4 / / CoNi2S4@CNT composite electrode material obtained in this comparative example 3 has serious morphology agglomeration, and the nanosheet layer has not been fully unfolded.

[0074] The electrochemical properties of the supercapacitor electrode were tested in the Chenhua CHI660E electrochemical workstation test system using the same test method as in Comparative Example 1. The supercapacitor electrode of Comparative Example 3 had a specific capacity of 1550 F / g at a current density of 1 A / g.

[0075] Comparative Example 4

[0076] This comparative example 4 is intended to investigate the effect of electrodeposition reaction time on the morphology of electrode materials. The method for preparing Co2NiO4 / / CoNi2S4@CNT composite electrode materials and assembling supercapacitors is the same as that of comparative example 1. Compared with comparative example 1, the electrodeposition reaction time in step (3) is adjusted from 1 h to 1.5 h, and other conditions remain unchanged.

[0077] As the electrodeposition reaction temperature increases, the gaps between the Co2NiO4 / / CoNi2S4@CNT nanosheets obtained in the comparative example of the present invention become smaller, and the nanosheet layers become closer.

[0078] The electrochemical properties of the supercapacitor electrode were tested in the Chenhua CHI660E electrochemical workstation test system using the same test method as in Comparative Example 1. The supercapacitor electrode of Comparative Example 4 had a specific capacity of 2935 F / g at a current density of 1 A / g.

[0079] Table 1: Performance comparison of Examples 1 to 4 and Comparative Examples 1 to 3

[0080] Serial number Specific capacity (F / g) Capacitance retention rate (%) Example 1 7247.9(1A / g) 79 (5A / g, 5000 cycles) Comparative Example 1 4840(1A / g) 82 (5A / g, 5000 cycles) Comparative Example 2 1896.19(1A / g) 76 (5A / g, 5000 cycles) Comparative Example 3 1550(1A / g) 72 (5A / g, 5000 cycles) Comparative Example 4 2935(1A / g) 70(5A / g, 5000 cycles)

[0081] In summary, the electrode material prepared by the present invention can be applied to supercapacitor electrodes and has high specific capacity and good cycle performance.

[0082] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A supercapacitor electrode material, characterized in that: include: A conductive substrate and a metal complex loaded on the conductive substrate; the metal complex is a nickel-cobalt-sulfur-oxygen complex, and the supercapacitor electrode material is a loose porous structure composed of three-dimensional nanosheets.

2. A supercapacitor electrode material according to claim 1, characterized in that: The nickel-cobalt-sulfur-oxygen composite is Co2NiO4 / / CoNi2S4@CNT, and the conductive substrate includes nickel foam.

3. A method for preparing a supercapacitor electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: The metal precursor is subjected to an electrodeposition reaction on a conductive substrate, and after washing and drying, the surface of the conductive substrate after the electrodeposition reaction is coated with a single-walled carbon nanotube slurry to obtain the supercapacitor electrode material.

4. The method for preparing a supercapacitor electrode material according to claim 3, characterized in that: The metal precursor is prepared by mixing cobalt nitrate and thiourea in a solvent, and the molar ratio of the cobalt nitrate to thiourea is in the range of (1-5): (5-10).

5. The method for preparing a supercapacitor electrode material according to claim 4, characterized in that: The cobalt nitrate and thiourea are mixed in a solvent by magnetic stirring for 20 to 45 minutes.

6. The method for preparing a supercapacitor electrode material according to claim 3, characterized in that: The electrodeposition reaction uses the metal precursor as an electrolyte, and deposits for 30 minutes to 90 minutes at a potential range of 6 to 20 V, an alternating current frequency of 40 Hz to 100 Hz, and a temperature of 25° C. to 50° C.

7. The method for preparing a supercapacitor electrode material according to claim 3, characterized in that: The coating of the single-walled carbon nanotube slurry comprises absorbing the single-walled carbon nanotube slurry to penetrate the surface of the conductive substrate after the electrodeposition reaction, and then vacuum drying to obtain the supercapacitor electrode material.

8. The method for preparing a supercapacitor electrode material according to claim 3, characterized in that: The single-walled carbon nanotube slurry is prepared by a CVD method, and the coating volume of the single-walled carbon nanotube slurry is 0.15 to 0.25 mL.

9. The method for preparing a supercapacitor electrode material according to claim 3, characterized in that: The conductive substrate is subjected to the following pretreatment steps: the conductive substrate is subjected to ultrasonic reaction in acid solution, acetone, deionized water and anhydrous ethanol in sequence.

10. A supercapacitor electrode, characterized in that: The electrode material comprises the electrode material according to any one of claims 1 to 2.

Citation Information

Patent Citations

  • Preparation method of NiCo<2>S<4> / carbon nanotube composite electrode material

    CN105023769A

  • NiCo2O4@NiCo2S4 core-shell nanowire array composite material and preparation method and application thereof

    CN107275123A

  • Preparation method and application of nickel sulfide / sulfur cobalt nickel / carbon nanotube foam

    CN109755036A

  • Method for preparing NiCo2O4@Ni-Co-S nanosheet array core-shell structure material

    CN109830377A

  • Co-Ni-S nanosheet material and preparation method and application thereof

    CN110233056A